2011
DOI: 10.2151/sola.2011-013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variations of Wet Deposition Flux of Mineral Dust in Japan

Abstract: To ascertain the temporal and spatial distribution of mineral dust deposition by wet processes, weekly deposition samples were obtained at Sapporo, Toyama, Nagoya, Tottori, Fukuoka, and Cape Hedo (Okinawa) during October 2008−January 2010 using automatic wet-dry separating samplers. Mineral dust weights in water-insoluble residue mixed with pollen were estimated from Fe contents measured using an X-ray fluorescence analyzer. Highest and lowest annual dust fluxes were found respectively at Toyama (8.7 g m −2 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Osada et al (2011) reported that the wet deposition of Asian dust in Japan is affected by the frequency of precipitation during dust seasons. Figure 3d shows the temporal variation in the precipitation amount during spring (February to March) observed at the Cordova station from the GHCN-Daily dataset (Manne et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osada et al (2011) reported that the wet deposition of Asian dust in Japan is affected by the frequency of precipitation during dust seasons. Figure 3d shows the temporal variation in the precipitation amount during spring (February to March) observed at the Cordova station from the GHCN-Daily dataset (Manne et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Possible sources of the iron supplied to the surface water of the northern North Pacific are deposition of mineral dust from the atmosphere (e.g., Duce and Tindale 1991) and mesoscale oceanic intrinsic processes, such as vertical winter mixing and horizontal Fe-rich intermediate water transport (Nishioka et al 2011). Several studies of mineral dust deposition using continuous multiyear observations have been conducted, especially in the Asian Continent and in Japan (e.g., Osada et al 2011). However, in remote areas, where the main source of iron to the sea surface is atmospheric dust, only short-term or sporadic monitoring observations had been conducted (e.g., Uematsu et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The Kosa has been often transported to Japan (e.g., Iwasaka et al 1983;Osada et al 2011;Yasunari et al 2016) and to remote regions such as the USA, Canada, Greenland, etc. (e.g., Rahn et al 1977;Biscaye et al 1997;McKendry et al 2001;Yasunari et al 2007;Yasunari and Yamazaki, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…go.jp/Takikawa/). Because the depolarization ratio is available, the lidar data can provide us the information on non-spherical particles such as dust particles (e.g., Shimizu et al 2004;Osada et al 2011;Yasunari et al 2016). We use the calculated dust and spherical extinction coefficients of the lidar data (Sugimoto et al 2003;Shimizu et al 2004) at Takikawa to confirm Kosa (dust) transports there (also see SI Text).…”
Section: Introductionmentioning
confidence: 99%
“…We have discussions on off-line LSM simulations including sensitivities and outputs from a global GEOS-5 simulation at a single location using the developed GOSWIM, including the total dust+BC+OC SDE. For validations, we use the unique observed data available in Sapporo, Japan, which include various Aoki et al 2013), and (4) total dust deposition flux during precipitation (called TDP) by Osada et al (2011). We considered EC as BC (see Section 2; SI).…”
Section: Introductionmentioning
confidence: 99%